Bilateral macronodular adrenocortical disease: a single centre experience - Anuj Ban; Rohit Barnabas; Manjiri Karlekar; Anurag Ranjan Lila; Chethan Yami Channaiah; Saba Samad Memon; Virendra A Patil; Vijaya Sarathi; Gwendolyn Fernandes; Hemangini Thakkar; Sameer Rege; Nalini S Shah; et al. (Endocrine Connections)
Background: Data on bilateral macronodular adrenocortical disease (BMAD) with respect to computed tomography (CT) scan characteristics (attenuation and washout) and long-term follow-up are limited. This study aims to describe BMAD patients managed in a single centre. Methods: BMAD was defined by the presence of bilateral adrenal macronodules (>1 cm) on CT. Clinical, biochemical, radiological, genetic characteristics, management and follow-up of 22 BMAD patients were studied retrospectively. Results: The median age (range) at presentation was 49.5 (23–83) years, predominantly observed in females (16/22). Eighteen (82%) patients were incidentally diagnosed (11 with mild autonomous cortisol secretion (MACS) and seven non-secretory), three (13.7%) presented with overt Cushing’s syndrome (CS), and one (4.5%) had androgen excess (without CS features). On CT, the dominant nodule’s median (range) size was 2.6(1.6–9.5) cm. 77.8% (14/18) of adrenal nodules were lipid-rich, and 93.3% (14/15) of the nodules exhibited good washout. Genetic analysis was available for eight patients; one had a novel germline ARMC5 variant, and two had MEN-1 gene mutations. Three overt CS and one androgen-secreting patient underwent total bilateral adrenalectomy; histopathology showed macronodular hyperplasia with internodular hypertrophy. Only one (1/8) patient from the MACS group developed a new comorbidity (diabetes mellitus) after a median follow-up of 6.4 (0.5–12.4) years, while none of the non-secretory group patients developed new comorbidities after a median follow-up of 1.4 (0.8–12.2) years. Conclusion: Most BMAD patients presented without overt hormonal excess, and none developed overt CS on follow-up. Detailed CT characteristics of BMAD nodules may help in radiological diagnosis in bilateral adrenal incidentalomas.